Selección de reproductores en base a los caracteres de importancia económica en la producción de leche de bovinos acorde al objetivo de mejora genética en la parroquia de Tanicuchí. - Chicaisa Ugsha, Jenifer Liseth (2023)
In the province of Cotopaxi, no genetic improvement program values the requirements of adaptability to the geographical reality of the province, which has resulted in generally inefficient milk production, as a result of blind selection. In 2019, the INEC estimated that around 4 Lt/h/d occurs in our country resulting in poor sustainability, in medium and small producers, based on the collected information (weight gain, production systems, health plan, mastitis test CMT, milk density and weighing), through quantitative research, with a deductive effect, the support of data collection techniques and instruments, they allowed to directly identify the life of the producers, facilitating the identification of the objectives of genetic improvement of the sector such as adaptability managing to have negative cows in mastitis, weight gain of 700g/d and milk quality (density) with a weight of 1.030, they were evaluated for their economic value in the dairy productions of the parish. The objective of the research was to objectively select the breeders that are suitable in the 3 selection criteria, where 6 cows were selected from a total of 62 cows in production, during the third stage of the program the cows will allow the dissemination of their genetic material, benefiting to all the medium and small producers on the sector.